Transcriptome Analysis of Arabidopsis thaliana in Response to Plasmodiophora brassicae during Early Infection - Zhao, Ying; Bi, Kai; Gao, Zhixiao; Chen, Tao; Liu, Huiquan; Xie, Jiatao; Cheng, Jiasen; Fu, Yanping; Jiang, Daohong (Frontiers in Microbiology, 2017)
Clubroot disease is a serious threat to cruciferous plants worldwide, especially to oilseed rape. However, knowledge on pathogenic molecular mechanisms and host interaction is limited. We presume that the recognition between Arabidopsis thaliana and Plasmodiophora brassicae occurs at the early stage of infection and within a relatively short period. In this study, we demonstrated changes on gene expression and pathways in A. thaliana during early infection with P. brassicae using transcriptome analysis. We identified 1903 and 1359 DEGs at 24 and 48 hours post inoculation (hpi), respectively. Flavonoids and the lignin synthesis pathways were enhanced, glucosinolates, terpenoids and proanthocyanidins accumulated and many hormonal- and receptor-kinase related genes were expressed, caused by P. brassicae infection during its early phase. Therefore, the early interaction between A. thaliana and P. brassicae plays an important role in the entire infection process. The results provide a new contribution to a better understanding of the interaction between host plants and P. brassicae, as well as the development of future measures for the prevention of clubroot.